Neurological complications of breast cancer: study protocol of a prospective cohort study. Issue 10 (28th October 2014) - Pereira, Susana; Fontes, Filipa; Sonin, Teresa; Dias, Teresa; Fragoso, Maria; Castro-Lopes, José; Lunet, Nuno
Abstract : Introduction: The improvement in breast cancer survival rates, along with the expected overdiagnosis and overtreatment associated with breast cancer screening, requires a comprehensive assessment of its burden. Neurological complications can have a devastating impact on these patients; neuropathic pain and chemotherapy-induced peripheral neuropathy are among the most frequently reported. This project aims to understand the burden of neurological complications of breast cancer treatment in Northern Portugal, and their role as mediator of the impact of the treatment in different dimensions of the patients' quality of life. Methods and analysis: A prospective cohort study was designed to include 500 patients with breast cancer, to be followed for 3 years. The patients were recruited at the Portuguese Oncology Institute of Porto and evaluations were planned at different stages: pretreatment, after surgery, after chemotherapy (whenever applicable) and at 1 and 3 years after enrolment. Patients diagnosed with neuropathic pain or chemotherapy-induced peripheral neuropathy (subcohorts), were also evaluated at the moment of confirmation of clinical diagnosis of the neurological complication and 6 months later. In each of the follow-up periods, a neurological examination has been performed by a neurologist. Data were collected on sociodemographic and clinical characteristics, quality of life, sleep quality, and anxiety and depression. Between January and December 2012, we recruited and conducted the baseline evaluation of 506 participants. The end of the follow-up period is scheduled for December 2015. Ethics and dissemination: The study protocol was approved by the Ethics Committee of the Portuguese Oncology Institute of Porto and all patients provided written informed consent. All study procedures were developed in order to assure data protection and confidentiality. Results from this project will be disseminated in international peer-reviewed journals and presented in relevant conferences.